“I’m not a person that reads”:: Identity Work, Adult Learners, and Educational (Dis)engagement - McLean, Scott; Dixit, Jaya (Canadian Journal of Education/Revue canadienne de l’éducation, 2018)
The concept of identity has become prominent in the study of Canadian education. We further the understanding of identity by examining the ways through which adults present themselves as subjects in learning processes. We recruited 134 adults who had recently read self-help books pertaining to health, careers, or relationships, and conducted qualitative interviews that focused on the motivations, goals, and learning outcomes that they attributed to their reading. We found that, during the process of being interviewed about their self-help reading experience, roughly half of our interviewees engaged in unsolicited “identity talk”—rhetorically embracing or distancing themselves from the social role of the self-help reader. Our study provides three key contributions to the scholarship of education: a nuanced ethnographic description of the complex and diverse ways in which adult learners position themselves as subjects in self-directed learning processes; an illustration of the theoretical utility and limitations of research focused on the identity work of individuals; and an exhortation to further research concerned with understanding the role of identity in processes of educational engagement/disengagement.